An experimental study on vertical motion control of a high-speed planing vessel using a controllable interceptor in waves. (1st February 2019) - Park, Jong-Yong; Choi, Hujae; Lee, Jooho; Choi, Hwiyong; Woo, Joohyun; Kim, Seonhong; Kim, Dong Jin; Kim, Sun Young; Kim, Nakwan
Abstract: This paper aims to construct an active control system using an interceptor and to verify the performance through towing tests to improve seakeeping performance of a high-speed planing vessel. The full-scale vessel is an unmanned surface vessel with a length of 8 m and the model ship is made with the scale ratio of 1/5.333. The interceptor servo unit is designed using the rack and pinion type. An embedded control system is developed based on a single board computer. The motion control algorithm is designed based on the differential control. The performance of the designed system and is verified by the calm water test and the seakeeping test in Seoul national university (SNU). The trim and the rise of center of gravity tend to decrease as the interceptor stroke increase. An improvement in the resistance by the interceptor is seen at the speed of less than Froude number 1.16. The pitch motion is decreased by 41.3% in the regular wave and 32.4% in the irregular wave by the controllable interceptor system. Highlights: This paper aims to construct an active motion control system using an interceptor and to verify the performance through towing tests. The full-scale vessel is an unmanned surface vessel with a length of 8 m and the model ship is made with a scale ratio of 1/5.333. An improvement in the resistance by the interceptor is seen at the speed of less than Froude number 1.16. The pitch motion is decreased by 41.3% in the regular wave and 32.4% in the irregular wave by the controllable interceptor system.